2012
DOI: 10.1007/s00127-012-0539-0
|View full text |Cite
|
Sign up to set email alerts
|

Conflict and mental health: a cross-sectional epidemiological study in Nepal

Abstract: Overall, the prevalence rates of depression and anxiety in the sample are comparable to, or lower than, other studies conducted with populations affected by conflict and with refugees. However, the findings underscore the need to address the current lack of mental health care resources in post-conflict rural Nepal, especially for marginalized populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
103
7
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(132 citation statements)
references
References 27 publications
14
103
7
2
Order By: Relevance
“…Women hypertensive patients were found to experience depression at a higher rate than men in several studies. [23][24][25][26] In the present study, the prevalence of depression among female patients was significantly higher than male patients. Taking antihypertensive medications has been previously found to be significantly associated with high BDI scores.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Women hypertensive patients were found to experience depression at a higher rate than men in several studies. [23][24][25][26] In the present study, the prevalence of depression among female patients was significantly higher than male patients. Taking antihypertensive medications has been previously found to be significantly associated with high BDI scores.…”
Section: Discussionsupporting
confidence: 42%
“…Similar to our study, other studies have found that increasing age is a predictor of depression among hypertensive Section: Medicine patients. [24][25][26] In the other hand, In Nigeria, a study had found no significant correlation between age and incidence of depression among patients attending the hypertensive clinic. Women hypertensive patients were found to experience depression at a higher rate than men in several studies.…”
Section: Discussionmentioning
confidence: 96%
“…Epidemiological estimates of community prevalence of the priority MNS disorders were available for the district neighbouring Sodo in Ethiopia [24][27]. In Chitwan (Nepal), community prevalence estimates were available for depression and other common mental disorders [28], and similarly for the North West province in which Dr KK district (South Africa) is located [29]. For the remaining MNS disorders and in the other PRIME sites, it was necessary to rely on extrapolation from national prevalence estimates (India, South Africa) or studies conducted in other LMICs (Uganda, Nepal).…”
Section: Resultsmentioning
confidence: 99%
“…This includes an environment where people are at increased risk of depression, anxiety and post-traumatic stress disorder [4]. Poverty, female gender discrimination and caste inequality are also causal factors that contribute to mental health problems such as depression [5].…”
Section: Introductionmentioning
confidence: 99%